Chemically engineering the drug release rate of a PEG-paclitaxel conjugate using click and steric hindrance chemistries for optimal efficacy. (October 2022) - Nguyen, Anne; Chao, Po-Han; Ong, Chun Yat; Rouhollahi, Elham; Fayez, Nojoud AL; Lin, Louis; Brown, Jennifer I.; Böttger, Roland; Page, Brent; Wong, Harvey; Li, Shyh-Dar
Abstract: A small molecule drug with poor aqueous solubility can be conjugated to a hydrophilic polymer like poly(ethylene glycol) (PEG) to form an amphiphilic polymer-drug conjugate that self-assembles to form nanoparticles (NPs) with improved solubility and enhanced efficacy. This strategy has been extensively applied to improve the delivery of several small molecule drugs. However, very few reports have succeeded to tune the rate of drug release from these NPs. To the best of our knowledge, there have been no reports of utilizing click and steric hindrance chemistry to modulate the drug release of self-assembling polymer-drug conjugates. In this study, we utilized click chemistry to conjugate methoxy-PEG (mPEG) to an anti-tumor drug, paclitaxel (PTX). A focused library of PTX-Rx-mPEG (x = 0, 1, 2) conjugates were synthesized with different chemical modalities next to the cleavable ester bond to study the effect of increasing steric hindrance on the self-assembly process and the physicochemical properties of the resulting PTX-NPs. PTX-R0-mPEG had no added steric hindrance (x = 0; minimal), PTX-R1-mPEG consisted of two methyl groups (x = 1: moderate), and PTX-R2-mPEG consisted of a phenyl group (x = 2: significant). Drug release studies showed that PTX-NPs released PTX at a decreased rate with increasing steric hindrance. Pharmacokinetic studies showed that the AUC of released PTX from the moderate-release PTX-R1-NP was approximately 20-, 6-, and 3-fold higher than that from free PTX, PTX-R0-NP and PTX-R2-NP, respectively. As a result, among these different PTX formulations, PTX-R1-NP showed superior efficacy in inducing tumor regression and prolonging the animal survival. The tumors treated with PTX-R1-NP displayed the lowest tumor progression markers (Ki68 and CD31) and the highest apoptotic marker (TUNEL) compared to the others. This work emphasizes the importance of taking a systematic approach in designing self-assembling polymer drug conjugates and highlights the potential of utilizing steric hindrance as a tool to tune the drug release rate from such systems.